2021
DOI: 10.3390/foods10010144
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Processing of Edible Orthopterans Provides a Highly Nutritive Source of Food Ingredients

Abstract: Edible orthopterans (grasshoppers, crickets, and locusts) are major delicacies, especially across sub-Saharan Africa. Their promotion as food ingredients is increasingly gaining momentum. This study evaluates the nutritional profiles of three widely consumed orthopterans: Gryllus bimaculatus, Locusta migratoria, and Schistocerca gregaria after blanching and oven-drying. All three species had high protein (65.3, 54.2, and 61.4% on a dry matter (DM) basis for G. bimaculatus, L. migratoria, and S. gregaria, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Processing methods are highly considered as one of the main factors influencing the quality and concentration of fats and fatty acids present in various insect species ( Fombong et al., 2021 ). Examples of techniques used in processing of edible insects includes cooking (steaming, roasting, smoking, frying, stewing, curing etc.…”
Section: The Effect Of Processing Methods On the Fatty Acid Compositi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Processing methods are highly considered as one of the main factors influencing the quality and concentration of fats and fatty acids present in various insect species ( Fombong et al., 2021 ). Examples of techniques used in processing of edible insects includes cooking (steaming, roasting, smoking, frying, stewing, curing etc.…”
Section: The Effect Of Processing Methods On the Fatty Acid Compositi...mentioning
confidence: 99%
“…Furthermore, the n-3 and n-6 fatty acids in orthopterans such as locusts and crickets ranges from (26.81 to 42.63 g/100g DM) and (11.35 to 13.40 g/100g DM) ( Table 1 ). Fombong et al . (2021) , also observed that the n-3 fatty acids such as α-linolenic acid is highly accumulated in locusts than common plant oils such as sunflower, olive and soybean.…”
Section: Accumulation Of Fats and Fatty Acids In Edible Insectsmentioning
confidence: 99%
“…Sucrose free medium showed less enzyme production naturally. There are many prior studies in the literature that were made by a mixture of edible insect extract with a usual medium component or in different food forms to present them as an alternative source (Belluco et al, 2013;Hamerman, 2016;Haber et al, 2019;Çabuk 2021;Fombong et al, 2021;), however, utilization of L. migratory as an effective substrate for microbial β-fructofuranosidase enzyme production has not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…Te traditional methods of harvesting grasshoppers/locusts were pointed out by respondents as majorly manual through chasing and handpicking and sometimes beating with twigs mostly performed in the morning when the insects are less mobile and in season. Tese methods are also similar to those used in other countries, for example, West Nigers [5] and Mexico [41]. A few of the respondents mentioned light traps and sweep nets as methods of harvesting grasshoppers and locusts.…”
Section: Availability In the Market Seasonal Occurrence Andmentioning
confidence: 93%